LANGKAH PENTING DALAM PENGENDALIAN EPIDEMI HIV YANG BERKELANJUTAN - Purba, Ivan Elisabeth; Sinaga, Taruli Rohana; Purba, Parlindungan (Program Studi Ners UNIVERSITAS SARI MUTIARA INDONESIA, 2020)
This research was conducted to determine the important steps in handling HIV Epidemic Cases. Three (3) stages must be carried out in controlling HIV, including (1) Improving health services, (2) Health education, and (3) Affordable financing. The location of this research was carried out in North Sumatra Province, especially in Medan City. The time this research was conducted was from August to December 2019. The samples in this study were taken as the selected information providers, namely leaders of community health centers, hospitals, health services, clinics, and heads of AIDS treatment and control. Based on the results of this research, it shows that if these three things are fulfilled, the cases of the HIV epidemic will decrease. Success or failure depends on satisfaction with the services provided, optimization, and support from professional health workers in their field. What is no less important is affordable financing from the government or private sector so that efforts to handle and control the HIV epidemic can be more effective, efficient, and targeted.